The little friend - Tartt, Donna, ....- (London : Bloomsbury, 2002)
Although the Cleves generally revelled in every detail of their family history, the events of 'the terrible Mother's Day' were never, ever discussed. On that day, nine-year-old Robin Cleves, loved by all for his whims and peculiarities, was found hanging by the neck from a rope slung over a black-tupelo tree in his own garden. Eleven years later, the mystery - with its taunting traces of foul play - was no nearer a solution than it had been on the day it happened.This isn't good enough for Robin's youngest sister Harriet. Only a baby when the tragedy occurred, but now twelve-years-old and steeped in the adventurous daring of favourite writers such as Stevenson, Kipling and Conan Doyle, Harriet is ready and eager to find and punish her brother's killer. Her closest friend Hely - who would try anything to make Harriet love him - has sworn allegiance to her call for revenge. But the world these plucky twelve-year-olds are to encounter has nothing to do with child's play: it is dark, adult and all too menacing. In Donna Tartt's Mississippi, the sense of place and sense of the past mingle redolently with rich human drama to create a collective alchemy. Here eccentric great aunts bustle about graciously despite faded fortunes and a child's inquiring mind not only unearths telling family artefacts, but stirs up a neighbourhood nest of vipers and larceny. THE LITTLE FRIEND is a profoundly involving novel which demonstrates how the imaginary life embraces what literature we read, what special places we inhabit and what kindred souls we recognize, to help crack open even the darkest secrets life has hiding for us.
Keywords: Fiction